2019
DOI: 10.3390/s19204496
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Assessment of Urinary and Fecal Volatile Organic Compound Analysis in De Novo Pediatric IBD

Abstract: Endoscopic evaluation is mandatory in establishing the diagnosis of pediatric inflammatory bowel disease (IBD), but unfortunately carries a high burden on patients. Volatile organic compounds (VOC) have been proposed as alternative, noninvasive diagnostic biomarkers for IBD. The current study aimed to assess and compare the potential of fecal and urinary VOC as diagnostic biomarkers for pediatric IBD in an intention-to-diagnose cohort. In this cohort study, patients aged 4–17 years, referred to the outpatient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
(54 reference statements)
0
7
0
1
Order By: Relevance
“…The diagnostic accuracy was slightly varied with the different techniques used or differing study groups ( Table 6 ) [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnostic accuracy was slightly varied with the different techniques used or differing study groups ( Table 6 ) [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…GC-IMS detected significantly different VOC profiles in 10 IBD patients vs. 10 controls ( p = 0.028, AUC = 0.78) [ 68 ]. This small study reported better performance of urinary-compared to fecal VOCs, as far as sensitivity was concerned (80% vs. 70%), but not for specificity (70% vs. 90%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, as the urine collecting method can be faster and more easily accepted by the patients, this type of establishing a preliminary diagnosis can accelerate the process. The distinction between the two methods is that analyses of fecal VOCs is believed to reflect the gut microbiota composition and local inflammatory processes, on the contrary, urinary VOCs associated with IBD are more likely to be a combination of compounds that diffused from the intestine into the bloodstream and VOCs that are associated with general inflammation [40]. Bosch et al previously used field asymmetric ion mobility spectrometry (FAIMS) to analyze fecal VOC composition as a potential tool in differentiating two gastro-intestinal conditions relying on the accessibility of the process in pediatric patients, achieving similar diagnostic accuracies [41].…”
Section: Volatile Organic Compounds (Voc)mentioning
confidence: 99%
“…Die VOC-Profile sowohl aus dem Stuhl (p-Wert 0,038; AUC 0,73) wie auch aus dem Harn (0,028, AUC 0,78) divergierten signifikant zwischen CED-Patienten und Kontrollprobanden. Die Profile wurden daher, ungeachtet der beiden Medien, aus denen sie analysiert wurden, hinsichtlich des Potenzials eines noninvasiven Biomarkers als für die pädiatrische CED-Diagnostik gleich gut eingestuft [23].…”
Section: Charakterisierung Der Mikrobiotadiversitätunclassified